2019
DOI: 10.1007/s00125-019-4951-9
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine programming of obesity and type 2 diabetes

Abstract: The type 2 diabetes epidemic and one of its predisposing factors, obesity, are major influences on global health and economic burden. It is accepted that genetics and the current environment contribute to this epidemic; however, in the last two decades, both human and animal studies have consolidated considerable evidence supporting the 'developmental programming' of these conditions, specifically by the intrauterine environment. Here, we review the various in utero exposures that are linked to offspring obesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
148
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(162 citation statements)
references
References 125 publications
1
148
0
1
Order By: Relevance
“…Accumulating evidence supports that adiposity may be epigenetically regulated and programmed in utero [31][32][33]. However, the biological pathways involved, as well as the influence of the various intrauterine exposures (e.g., maternal obesity and GDM) on epivariations "programming" are yet to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence supports that adiposity may be epigenetically regulated and programmed in utero [31][32][33]. However, the biological pathways involved, as well as the influence of the various intrauterine exposures (e.g., maternal obesity and GDM) on epivariations "programming" are yet to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…Besides signaling events, various studies have revealed epigenetic mechanisms underlying changes in fetal gene expression in response to an altered intrauterine environment. Such epigenetic mechanisms include DNA methylation and translational repression by miRNAs (reviewed by [35]). In fact, both mechanisms occur in MME regulation: Increased DNA methylation of the MME promoter region was observed in Alzheimer's disease brain [36] and in several types of cancer, such as leukemia [37] and breast cancer [38].…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic risk factors The influence of epigenetic risk factors on the development of type 2 diabetes in youth and on cardiometabolic risk across the life span is a rapidly emerging area of research highlighted elsewhere in this special issue by Fernandez-Twinn et al [49] and in other recent reviews [50,51]. In brief, a few themes emerge in the preclinical data that align with clinical data on sex-specific effects of specific epigenetic factors (reviewed in [50][51][52]).…”
Section: Mechanism Of Type 2 Diabetes Onset In Youthmentioning
confidence: 99%